Challenges and Opportunities for the Adoption of Smart Greenhouses: Analysis in Costa Rica Agriculture - Aguilar Pereira, José Francisco (2026)
The successful incorporation of advanced technologies is a key challenge in modern agriculture to address climate change and the growing global demand for food. This study evaluated the potential implementation of climate-smart greenhouses (CSGs) in Costa Rica through four case studies focused on agroclimatic, technological, infrastructural, and market aspects. The methodology included a literature review and farm visits to interview agricultural producers and professionals specializing in greenhouse horticultural production. The findings demonstrated that CSGs can increase productivity by up to 30%, reduce water use by 40 %, and enhance agricultural resilience. However, this success depends on the effective integration of agroclimatic, technological, financial, and market factors. It is essential to develop collaborative strategies among public, private, and academic entities to implement pilot projects in tropical conditions for the validation and adoption of CSGs technologies while training professionals and producers. In conclusion, the successful implementation of CSGs requires precise technological and agronomic validation, a comprehensive approach to key factors, public policy support, and technical training for the agricultural sector.